Suppression of Weeds and Increases in Food Production in Higher Crop Diversity Planting Arrangements: A Case Study of Relay Intercropping. Issue 4 (10th May 2018) - Su, Benying; Liu, Xin; Cui, Liang; Xiang, Bao; Yang, Wenyu
Abstract : Crop diversification plays an important role in increasing land use efficiency and weed suppression. A field experiment was conducted on maize ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] relay intercropping and corresponding monocultures in Southwest China in 2012 to 2013. Differences were observed in crop productivity, weed diversity, and weed biomass. Grain yield and aboveground biomass for maize did not differ between intercropped and monocultured maize; however, they were lower for soybean in intercropping compared to soybean in monoculture (SM). Greater decreases were evident for the intercropping of one row of soybean alternated with one row of maize (MSRI1) (−46% for yield and −55% for biomass) than the intercropping of two rows of soybean alternated with two rows of maize (MSRI2) (−10% for yield and −27% for biomass). The total grain yield and aboveground biomass in MSRI2 were higher than those in MSRI1 (5.9% for yield and 6.4% for biomass), monoculture maize (MM, 16% for yield and 24% for biomass), and SM (394% for yield and 227% for biomass). Weed diversity and biomass in the intercropped phase were lower in MSRI1 and MSRI2 than in MM and SM, and the total weed biomass during the entire growing season also decreased in intercropping as compared with monocultures and fallow, with decreases of 28, 40, and 60% in MSRI1 and 29, 41, and 61% in MSRI2 compared with MM, SM, and fallow, respectively. In addition, more light was also captured by intercrops than by those in monoculture and fallow. Correlation analysis suggested that crop diversity suppressed weed growth by increasing the interception of light by crops.